Estimating parties' left-right positions: Determinants of voters' perceptions' proximity to party ideology. (March 2016) - Busch, Kathrin Barbara
Abstract: The article aims to explore whether the accuracy of voters' perceptions of party ideology are affected by party position shifts and by the media's turn to non-left-right issues, such as political leadership, during election campaigns. Using data from the Comparative Study of Electoral Systems (CSES) and a country-specific left-right index based on data by the Comparative Manifestos Project (CMP), multilevel analyses reveal that emphasizing leadership issues can lead voters to reflect left-right positions more accurately. A party's left-right position shift between elections does not lead to a significant difference in voters' perceptions, while a shift on the economic sub-dimension of left-right ideology can even lead voters to more position clarity. However, multiple parties' shifting their positions seems to overburden respondents' cognitive capacity. Highlights: A multilevel analysis of voters' perceptions of party ideology in Western democracies and Eastern European EU member states. Multiple parties' position shifts between elections decrease voters' estimation accuracy. A single party's position shift on the economic sub-dimension leads to more accurate estimations. Saliency on leader personality evaluation increases voters' estimation proximity to parties' ideological positions.